Dark matter and lepton flavour phenomenology in a singlet-doublet scotogenic model - Maud Sarazin; Jordan Bernigaud; Björn Herrmann (Journal of High Energy Physics, 2021)
Abstract We study the dark matter phenomenology of scotogenic frameworks through a rather illustrative model extending the Standard Model by scalar and fermionic singlets and doublets. Such a setup is phenomenologically attractive since it provides the radiative generation of neutrino masses, while also including viable candidates for cold dark matter. We employ a Markov Chain Monte Carlo algorithm to explore the associated parameter space in view of numerous constraints stemming from the Higgs mass, the neutrino sector, dark matter, and lepton-flavour violating processes. After a general discussion of the results, we focus on the case of fermionic dark matter, which remains rather uncovered in the literature so far. We discuss the associated phenomenology and show that in this particular case a rather specific mass spectrum is expected with fermion masses just above 1 TeV. Our study may serve as a guideline for future collider studies.